Three-dimensional interval woven fabric reinforced SiO2 aerogel composite material as well as preparation method and application thereof

By using modified three-dimensional spacer woven fabrics as reinforcement materials in SiO2 aerogels, the problem of fragility of aerogels is solved, significantly improving its mechanical properties and making it suitable for applications as a thermal insulation material.

CN119638365APending Publication Date: 2025-03-18TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411831141.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The brittle and fragile properties of SiO2 aerogels due to its low connection strength between the skeleton particles limit its large-scale promotion in various applications.

Method used

The surface of the woven fabric was modified by seed-induced solvothermal method to grow TiO2 nanoarrays, and the composite silicon source was used to prepare a reinforced SiO2 aerogel composite material by sol-gel method.

Benefits of technology

It significantly improves the mechanical properties of the composite material, while retaining the original excellent structural and physical properties of the aerogel, making it suitable for widespread applications as a thermal insulation material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638365A_ABST
    Figure CN119638365A_ABST
Patent Text Reader

Abstract

The invention discloses a three-dimensional interval woven fabric reinforced SiO2 aerogel composite material as well as a preparation method and application thereof, and belongs to the technical field of aerogel preparation. The three-dimensional interval woven fabric reinforced SiO2 aerogel composite material is prepared by the following steps: firstly, carrying out surface modification on a three-dimensional interval woven fabric by utilizing a seed induction solvothermal method, so that a TiO2 nano array grows on the surface of the three-dimensional interval woven fabric, and obtaining a modified three-dimensional interval woven fabric; and then by taking methyltrimethoxysilane and tetraethoxysilane as composite silicon sources and the modified three-dimensional spacer woven fabric as a reinforcing material, preparing the three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material by utilizing a sol-gel method. According to the reinforced SiO2 aerogel composite material prepared by the preparation method disclosed by the invention, the modified three-dimensional spacer woven fabric is used as a reinforcing material, so that the original structure and performance advantages of aerogel are reserved to a greater extent while the mechanical property of the aerogel is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aerogel preparation, and in particular relates to a three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material and a preparation method and application thereof. Background Art

[0002] Aerogel is a lightweight material with a nanoporous structure, which has attracted much attention due to its unique physical and chemical properties. The low density (almost 90% of the total volume is composed of air), low thermal conductivity and large specific surface area of ​​this material are its remarkable characteristics. Aerogel is usually prepared by the sol-gel method, that is, a wet gel is first formed, and the liquid phase material in the wet gel is removed through aging, solvent replacement, hydrophobic modification, drying and other steps to form an aerogel. Therefore, the large area of ​​pores in the aerogel is retained after the internal liquid phase material is removed from the wet gel, and finally a porous skeleton structure is formed, which has a nanoscale three-dimensional mesh pore structure.

[0003] SiO2 aerogel has a wide range of applications, including but not limited to electronics, construction, aerospace, water and air purification, sensing, catalysts, biomedicine, absorbents, food packaging and textiles. In the field of thermal insulation, SiO2 aerogel is known as a new super thermal insulation composite material due to its low thermal conductivity, high porosity and large specific surface area. In the field of thermal insulation, SiO2 aerogel can achieve the same thermal insulation effect as traditional composite materials with lighter weight and smaller volume, and has shown application potential in aerospace, military and civilian fields. In addition, the optical transparency of SiO2 aerogel also makes it useful in the optical field, such as optical anti-reflection film for optical components of high-power laser systems, display devices and solar cell protective glass. In the electrical field, the ultra-low dielectric constant of SiO2 aerogel makes it applicable to high-temperature wave-transmitting materials for missiles. In the field of catalysis, its high specific surface area and porous structure make it an ideal material for loading catalysts, with superior activity, selectivity and lifespan over traditional catalysts. In the medical field, the high porosity and biocompatibility of SiO2 aerogels make them potential for application in biomedical fields, such as drug delivery and controlled release systems.

[0004] However, SiO2 aerogel is brittle and fragile due to its low strength of connection between skeleton particles, which limits its application in various applications and prevents its large-scale promotion and use. Therefore, improving the mechanical properties of SiO2 aerogel by strengthening and toughening it is the key to realizing its large-scale engineering application. At present, the main strengthening methods are: self-reinforcement, polymer reinforcement, fiber reinforcement, etc. Among them, self-reinforcement and polymer reinforcement have limited mechanical strengthening effects on aerogels, and the process is relatively complicated; when short-cut fibers are used to strengthen aerogels, the fibers are unevenly dispersed, the bridging effect between fibers is small, it is difficult to form a whole, and the interface bonding ability between fibers and aerogel matrix is ​​weak, and the mechanical properties are limited. When fiber felt is used to strengthen aerogel, due to the large volume density of fiber felt, little space is reserved for aerogel, and the original structure and performance of aerogel are greatly damaged. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material and a preparation method and application thereof.

[0006] The first aspect of the present invention provides a method for preparing a three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material. First, the three-dimensional spacer woven fabric is surface modified by a seed-induced solvent thermal method so that a TiO2 nanoarray grows on the surface of the three-dimensional spacer woven fabric to obtain a modified three-dimensional spacer woven fabric; then, methyltrimethoxysilane and tetraethoxysilane are used as a composite silicon source and the modified three-dimensional spacer woven fabric is used as a reinforcing material to prepare the three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material by a sol-gel method.

[0007] The three-dimensional spacer woven fabric used in the present invention has good integrity, and the mechanical properties of the reinforced composite material are significantly improved, and its "quasi-hollow" structure can retain the original excellent structure and physical properties of the aerogel to a large extent; then, the three-dimensional spacer woven fabric is surface modified by tetrabutyl titanate, so that TiO2 nanoarrays grow on the surface of the three-dimensional spacer woven fabric, the TiO2 nanoarrays increase the surface roughness of the fiber, increase the specific surface area, and the TiO2 nanoarrays can enhance the interface bonding between the fiber and the aerogel matrix through mechanical locking, and at the same time, combined with the fiber reinforcement effect, improve the mechanical properties of the aerogel; then, MTMS (methyltrimethoxysilane) and TEOS (tetraethoxysilane) are used as composite silicon sources, and the advantages of the two are utilized to prepare an aerogel matrix with good comprehensive performance.

[0008] In an optional embodiment, the molar ratio of methyltrimethoxysilane to tetraethoxysilane is 1:(0.5-2).

[0009] Preferably, the molar ratio of methyltrimethoxysilane to tetraethoxysilane is 1:1.

[0010] Preferably, the preparation steps of the modified three-dimensional spacer woven fabric include:

[0011] (1) adding melamine and nitric acid to a H2O2 solution, stirring until it becomes clear, adding a titanium sheet and stirring until a reddish brown precursor solution 1 is obtained;

[0012] (2) adding tetrabutyl titanate (TBOT) dropwise into a hydrochloric acid aqueous solution, stirring and hydrolyzing until clear, to obtain a precursor solution 2;

[0013] (3) immersing the three-dimensional spacer woven fabric (fiber preform) in the precursor solution 2, placing it at an angle, performing a hydrothermal reaction, washing, drying, and performing a first heat treatment in an oxygen-containing atmosphere to obtain a three-dimensional spacer woven fabric with a TiO2 seed layer uniformly loaded on the fiber surface;

[0014] (4) Immersing the three-dimensional spacer woven fabric with a TiO2 seed crystal layer on its surface in the precursor solution 1, heating for reaction, repeatedly filtering and injecting new precursor solution 1, drying after the reaction is complete, and performing a second heat treatment to obtain the modified three-dimensional spacer woven fabric.

[0015] In an optional solution, the molar ratio of methyltrimethoxysilane to tetraethoxysilane is 1:(0.5-2); and the oxygen-containing atmosphere is an air atmosphere.

[0016] Preferably, the temperature of the first heat treatment is 450° C. and the time is 6 hours.

[0017] In an optional scheme, the concentration of the hydrochloric acid in step (2) is 26.7 Vol%; the volume ratio of the tetrabutyl titanate and the hydrochloric acid aqueous solution is 1:30; and / or the hydrolysis time is 2 hours.

[0018] Optionally, the conditions of the hydrothermal reaction are: reacting in an environment of 120-140° C. for 14-16 hours; and / or, the temperature of the second heat treatment is 450-600° C., and the time is 6-7 hours.

[0019] Preferably, the conditions of the hydrothermal reaction are: reaction in an environment of 120° C. for 16 hours; and / or the temperature of the second heat treatment is 450-600° C. and the time is 6 hours.

[0020] In an optional scheme, the preparation steps of the three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material by the sol-gel method include: (1) adding acid to the composite silicon source solution to adjust the pH value to 2-3, heating and hydrolyzing to obtain a hydrolyzate; (2) dripping DMF dropwise into the hydrolyzate under stirring conditions, and then adding alkali to adjust the pH value of the hydrolyzate to 8-9; (3) placing the modified three-dimensional spacer woven fabric into a mold, pouring in the hydrolyzate, stirring evenly and letting it stand to gel, and then aging; (4) washing the aged gel and hydrophobically modifying it; (5) drying to obtain the three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material.

[0021] In an optional solution, the hydrolysis temperature is 40° C. and the time is 30 min; and / or

[0022] The aging conditions are: adding the gel to an aging solution with a volume ratio of TEOS to ethanol of 1:1 at 50°C for 72 hours; and / or the hydrophobic modification solution is a mixed solution of TMCS, ethanol, and n-hexane with a volume ratio of 2:1:7, and the modification time is 72 hours; and / or the drying conditions in step (5) are: placing the wet gel in a forced air drying oven, drying at 60°C for 6 hours and at 80°C for 6 hours. The purpose of stepwise drying is to prevent the internal network structure of the gel from expanding and being damaged due to a sudden increase in temperature during the drying process.

[0023] The second aspect of the present invention is to provide a three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material.

[0024] The third aspect of the present invention is to provide the application of the above-mentioned three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material as a thermal insulation material. Since the three-dimensional spacer woven fabric used in the present invention has good integrity, the mechanical properties of the reinforced composite material are significantly improved, and its "quasi-hollow" structure can retain the original excellent structure and physical properties of the aerogel to a large extent. After modification, the mechanical properties of the aerogel prepared with the composite silicon source are enhanced, so it can be widely used as a thermal insulation material.

[0025] The present invention has the following technical effects:

[0026] The three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material prepared by the present invention uses the modified three-dimensional spacer woven fabric as a reinforcing material, which not only retains the excellent properties of the aerogel itself, but also enhances the mechanical properties of the gel composite material by improving the interfacial bonding force between the fiber and the gel matrix. The product of the present invention has low raw material price, simple production process, and is easy to realize industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0028] Figure 1 A physical picture of the three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material prepared in Example 1;

[0029] Figure 2 This is a physical picture of the aerogel material prepared in Comparative Example 6;

[0030] Figure 3 The preparation flow chart of the three-dimensional spacer woven fabric reinforced silica aerogel composite material according to the embodiment of the present invention is as follows: (a) three-dimensional spacer woven fabric structure; (b) TiO2 nanoarrays grown on the fabric surface; (c) three-dimensional spacer woven fabric / TiO2 / aerogel composite material; wherein, 1-ground warp yarn; 2-weft yarn; 3-spacer sand; 4-TiO2 nanoarrays grown on the fiber surface; 5-SiO2 aerogel matrix;

[0031] Figure 4 This is a scanning electron microscope image of the fiber before modification of the three-dimensional spacer woven fabric in Example 1;

[0032] Figure 5 The scanning electron microscope image (10 μm) of the modified fiber of the three-dimensional spacer woven fabric;

[0033] Figure 6 This is a scanning electron microscope image of the fibers of the spacer woven fabric before modification (1 μm). DETAILED DESCRIPTION

[0034] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0035] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0036] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0037] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0038] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0039] like Figure 3 As shown, an embodiment of the present invention discloses a method for preparing a three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material. First, the three-dimensional spacer woven fabric is surface modified by a seed-induced solvent thermal method, so that a TiO2 nanoarray grows on the surface of the three-dimensional spacer woven fabric to obtain a modified three-dimensional spacer woven fabric; then, methyltrimethoxysilane and tetraethoxysilane are used as a composite silicon source, and the modified three-dimensional spacer woven fabric is used as a reinforcing material to prepare the three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material by a sol-gel method.

[0040] As an illustration, the three-dimensional spacer woven fabric used in the embodiment of the present invention is a glass fiber three-dimensional spacer woven fabric, which is a three-dimensional structural fabric composed of a plurality of spacer yarns (alkali-free glass fiber material) connecting the upper and lower surface fabric layers. The spacer yarns support the two surface fabric layers to form a spacer layer of a certain thickness. This special three-dimensional structure allows a large amount of still air to be stored in the spacer layer, and still air is the medium with the smallest thermal conductivity in nature, making it have better thermal insulation performance than ordinary single-layer fabrics, and there is great room for development as a high-performance thermal insulation material.

[0041] The benefits of using methyltrimethoxysilane (MTMS) and tetraethoxysilane (TEOS) as composite silicon sources to prepare aerogels are mainly reflected in the following aspects: 1. Improving the performance of aerogels: (1) Methyltrimethoxysilane has a non-hydrolyzable -CH3 group. The aerogels synthesized with this as a precursor have large pores and loose structures, so they have good elasticity, but they have problems such as small specific surface area and large pore size distribution; the aerogels prepared with tetraethoxysilane as a silicon source have high specific surface area and uniform pore size distribution, but their rigid structure leads to poor flexibility and fragility. Using MTMS and TEOS as co-precursors, by adjusting the ratio of the two, an aerogel matrix with good comprehensive performance can be obtained; (2) Optimizing thermal stability and flame retardancy. The composite use of methyltrimethoxysilane and tetraethoxysilane can affect the microstructure of silica aerogels by adjusting their ratio, thereby optimizing their thermal stability and flame retardancy. 2. Regulating the microstructure of aerogels: (1) Controlling hydrolysis and condensation reactions. In the sol-gel process, methyltrimethoxysilane and tetraethoxysilane are used as precursors to undergo hydrolysis and condensation reactions under the action of acid-base catalysts. By adjusting parameters such as acidity and alkalinity, reaction temperature, etc., the hydrolysis and condensation reactions can be controlled to obtain a more uniform gel network. (2) Influencing porosity and specific surface area. The use of composite silicon sources can also affect the porosity and specific surface area of ​​aerogels. By adjusting the ratio of methyltrimethoxysilane and tetraethoxysilane, aerogels with different porosities and specific surface areas can be prepared to meet the application requirements of different fields. 3. Improving the controllability and efficiency of the preparation process: (1) Simplifying the preparation process. Methyltrimethoxysilane and tetraethoxysilane are used as composite silicon sources to simplify the preparation process of aerogels. For example, by combining the acid-base two-step catalytic sol-gel method and surface hydrophobic modification, block-shaped nanoporous amorphous silicon aerogel can be prepared under normal pressure drying, reducing the preparation cost; (2) Improving preparation efficiency. The use of composite silicon sources can also improve the preparation efficiency of aerogels. By optimizing preparation conditions, such as reaction temperature, catalyst concentration, etc., the preparation cycle can be shortened and production efficiency can be improved.

[0042] In some embodiments, the molar ratio of methyltrimethoxysilane to tetraethoxysilane is 1:(0.5-2); the oxygen-containing atmosphere is an air atmosphere. The optimal ratio is obtained through experimental screening in the embodiments of the present invention, that is, the molar ratio of methyltrimethoxysilane to tetraethoxysilane is 1:1. The comprehensive performance of the aerogel composite material prepared at this ratio is better.

[0043] In some embodiments of the present invention, a seed-induced solvothermal method is used to modify a three-dimensional spacer woven fabric, that is, the three-dimensional spacer woven fabric is immersed in a saline solution of tetrabutyl titanate, and TiO2 seed crystals are grown on the fiber surface through a solvothermal reaction. Then, the three-dimensional spacer woven fabric is added to a titanium precursor solution, and a solvothermal reaction is performed again to grow a TiO2 nanoarray in situ on the TiO2 seed crystals.

[0044] The preparation steps of the modified three-dimensional spacer woven fabric include:

[0045] (1) adding melamine and nitric acid to a H2O2 solution, stirring until it becomes clear, adding a titanium sheet and stirring until a reddish brown precursor solution 1 is obtained;

[0046] (2) adding tetrabutyl titanate dropwise to an aqueous hydrochloric acid solution, stirring and hydrolyzing until clarified, to obtain a precursor solution 2; (3) immersing a fiber preform (three-dimensional spacer woven fabric) in the precursor solution 2, placing it at an angle, performing a hydrothermal reaction, washing, drying, and performing a first heat treatment in an oxygen-containing atmosphere to obtain a fiber preform having a TiO2 seed crystal layer uniformly loaded on the fiber surface;

[0047] (4) Immersing the preform with the TiO2 seed crystal layer on the surface in the precursor solution 1, heating for reaction, repeatedly filtering and injecting new precursor solution 1, drying after the reaction is complete, and performing a second heat treatment to obtain the modified three-dimensional spacer woven fabric.

[0048] In some preferred embodiments of the present invention, the temperature of the first heat treatment is 450° C. and the time is 6 hours; and / or the oxygen-containing atmosphere is an air atmosphere.

[0049] In some preferred embodiments of the present invention, the concentration of the hydrochloric acid in step (2) is 26.7 Vol%; the volume ratio of the tetrabutyl titanate and the hydrochloric acid aqueous solution is 1:30; and the hydrolysis time is 2 h.

[0050] In some embodiments, the conditions of the hydrothermal reaction are: reacting in an environment of 120-140° C. for 14-16 hours; the temperature of the second heat treatment is 450-600° C., and the time is 6-7 hours.

[0051] In some preferred embodiments of the present invention, the conditions of the hydrothermal reaction are: reaction in an environment of 120° C. for 16 hours; the temperature of the second heat treatment is 450-600° C., and the time is 6 hours.

[0052] In some preferred embodiments of the present invention, the steps for preparing the three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material by the sol-gel method include: (1) adding acid to the composite silicon source solution to adjust the pH value to 2-3, heating and hydrolyzing to obtain a hydrolyzate; (2) dripping DMF dropwise into the hydrolyzate under stirring conditions, and then adding alkali to adjust the pH value of the hydrolyzate to 8-9; (3) placing the modified three-dimensional spacer woven fabric into a mold, pouring in the hydrolyzate, stirring evenly and letting it stand to gel, and then aging; (4) washing the aged gel and hydrophobically modifying it; (5) drying to obtain the three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material.

[0053] In some preferred embodiments of the present invention, the hydrolysis temperature is 40° C. and the time is 30 min.

[0054] In some preferred embodiments of the present invention, the gel is added to an aging solution with a volume ratio of TEOS to ethanol of 1:1 at 50°C and aged for 72 hours; in some preferred embodiments of the present invention, the hydrophobically modified modification solution is a mixed solution of TMCS, ethanol and n-hexane in a volume ratio of 2:1:7, and the modification time is 72 hours; in some preferred embodiments of the present invention, the drying conditions in step (5) are: the wet gel is placed in a forced air drying oven and dried at 60°C for 6 hours and at 80°C for 6 hours.

[0055] It should be noted that the technical means not shown in the embodiments of the present invention may be conventional technical means in the art, and the present invention is not limited thereto.

[0056] The raw materials used in the following examples of the present invention were purchased from conventional sources.

[0057] The normal temperature in the embodiment of the present invention is 25±2°C.

[0058] Example 1

[0059] A method for preparing a three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material, the preparation steps are as follows:

[0060] S1. Surface modification of three-dimensional spacer woven fabric: (1) At room temperature, add 0.2g melamine and 2ml nitric acid to 100ml H2O2 solution, stir for 2h until clear, add 5g titanium sheet and stir for 48h to obtain reddish brown precursor solution 1; (2) At room temperature, add TBOT dropwise to hydrochloric acid aqueous solution (hydrochloric acid concentration is 26.7Vol%, volume ratio of TBOT to hydrochloric acid aqueous solution is 1:30), stir for 2h to hydrolyze until clear, and obtain precursor solution 2; (3) Pour precursor solution 2 into a hydrothermal reactor so that precursor solution 2 occupies 60% of the volume of the lining, immerse the fiber preform (three-dimensional spacer woven fabric) in precursor solution 2, and pour Place it at an angle, then place the autoclave in an environment of 120°C to react for 16 hours; wash the fiber preform after the reaction with deionized water until it is neutral, dry it at 100°C for 4 hours, and then heat treat it in air at 450°C for 6 hours to obtain a fiber preform with a TiO2 seed layer uniformly loaded on the fiber surface; (4) immerse the preform with the TiO2 seed layer on the surface in precursor solution 1, react at 80°C, filter it every 4 hours and re-inject new precursor solution 1, after reacting for 24 hours, take it out and wash it with distilled water until it is neutral, dry it at 100°C for 4 hours, and then heat treat it at 450°C for 7 hours to obtain a modified three-dimensional spacer woven fabric. The scanning electron microscope image of the fiber is shown in Figure 5 and Figure 6 It can be seen that the TiO2 formed is nanoflowers, which is smaller than that before modification (such as Figure 4 The specific surface area is greatly increased.

[0061] S2. Preparation of three-dimensional spacer woven fabric / SiO2 aerogel composites: (1) Deionized water, ethanol, TEOS, and MTMS were mixed in a molar ratio of 10:4:1:1 and stirred magnetically at room temperature to make the mixture uniform; (2) 1 ml of oxalic acid solution (0.1 mol·L) was added dropwise. -1 ) The pH value of the mixed solution was controlled at 2, and the mixed solution was sealed and placed in a 40°C water bath environment for heating and magnetic stirring for 30 min to hydrolyze the solution to obtain a sol hydrolyzate; (3) DMF (DMF to TEOS molar ratio is 0.5) was added dropwise into the sol hydrolyzate and magnetic stirring was performed for 5 min to mix evenly; 0.5 ml of ammonia solution (0.5 mol·L -1) Make the pH value 9, put the three-dimensional spacer woven fabric into the mold, pour in the sol hydrolyzate, stir evenly and let it stand to gel, wait until the beaker is tilted at 45℃ and the liquid surface does not flow, add TEOS and ethanol in a volume ratio of 1:1 aging solution and age for 72h (50℃); (4) After aging, rinse with n-hexane for 4 times, each time for 6h. After rinsing, place the wet gel in a mixed solution of TMCS, ethanol and n-hexane in a volume ratio of 2:1:7 for hydrophobic modification for 72h (50℃). When the wet gel is suspended in the modification solution, the modification is completed; (5) Finally, place the wet gel in a blast drying oven, dry it at 60℃ for 6h, and dry it at 80℃ for 6h to obtain a three-dimensional spacer woven fabric / SiO2 aerogel composite material. See the actual picture Figure 1 .

[0062] Example 2

[0063] A method for preparing a three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material, the preparation steps are as follows:

[0064] S1. Surface modification of three-dimensional spacer woven fabric: (1) At room temperature, 0.2 g of melamine and 2 ml of nitric acid were added to 100 ml of H2O2 solution, stirred for 2 h until clear, and 5 g of titanium sheet was added and stirred for 48 h to obtain a reddish-brown precursor solution 1; (2) At room temperature, TBOT was added dropwise to a hydrochloric acid aqueous solution (the hydrochloric acid concentration was 26.7 Vol%, and the volume ratio of TBOT to the hydrochloric acid aqueous solution was 1:30), stirred for 2 h to hydrolyze until clear, and a precursor solution 2 was obtained; (3) Precursor solution 2 was poured into a hydrothermal reactor so that precursor solution 2 occupied 60% of the volume of the lining, and the fiber preform (three-dimensional spacer woven fabric) was immersed in the precursor solution. Liquid 2, placed at an angle, and then placed the autoclave in an environment of 140°C to react for 14 hours; the fiber preform after the reaction was washed with deionized water until neutral, dried at 100°C for 4 hours, and then heat treated at 500°C in air for 5 hours to obtain a fiber preform with a TiO2 seed layer uniformly loaded on the fiber surface; (4) The preform with a TiO2 seed layer on the surface was immersed in precursor solution 1, reacted at 80°C, filtered and re-injected with new precursor solution 1 every 4 hours, reacted for 24 hours, taken out, washed with distilled water until neutral, dried at 100°C for 4 hours, and then heat treated at 500°C for 6 hours to obtain a modified three-dimensional spacer woven fabric.

[0065] S2. Preparation of three-dimensional spacer woven fabric / SiO2 aerogel composites: (1) Deionized water, ethanol, TEOS, and MTMS were mixed in a molar ratio of 10:4:2:1 and stirred magnetically at room temperature to make the mixture uniform; (2) 1 ml of oxalic acid solution (0.1 mol·L) was added dropwise. -1) The pH value of the mixed solution was controlled at 2, and the mixed solution was sealed and placed in a 40°C water bath environment for heating and magnetic stirring for 30 min to hydrolyze the solution to obtain a sol hydrolyzate; (3) DMF (DMF to TEOS molar ratio is 0.5) was added dropwise into the sol hydrolyzate and magnetic stirring was performed for 5 min to mix evenly; 0.5 ml of ammonia solution (0.5 mol·L -1 ) to make the pH value 9, put the three-dimensional spacer woven fabric into the mold, pour in the sol hydrolyzate, stir evenly and let it stand to gel, wait until the beaker is tilted at 45℃ and the liquid surface does not flow, then add it into an aging solution with a volume ratio of TEOS to ethanol of 1:1 and age it for 72h (50℃); (4) After the aging is completed, rinse it repeatedly with n-hexane for 4 times, each time for 6h. After the rinsing is completed, place the wet gel in a mixed solution of TMCS, ethanol and n-hexane with a volume ratio of 2:1:7 for hydrophobic modification for 72h (50℃). When the wet gel is suspended in the modification solution, the modification is completed; (5) Finally, place the wet gel in a forced air drying oven, dry it at 60℃ for 6h and at 80℃ for 6h to obtain a three-dimensional spacer woven fabric / SiO2 aerogel composite material.

[0066] Example 3

[0067] A method for preparing a three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material, the preparation steps are as follows:

[0068] S1. Surface modification of three-dimensional spacer woven fabric: (1) At room temperature, 0.2 g of melamine and 2 ml of nitric acid were added to 100 ml of H2O2 solution, stirred for 2 h until clear, and 5 g of titanium sheet was added and stirred for 48 h to obtain a reddish-brown precursor solution 1; (2) At room temperature, TBOT was added dropwise to a hydrochloric acid aqueous solution (the hydrochloric acid concentration was 26.7 Vol%, and the volume ratio of TBOT to the hydrochloric acid aqueous solution was 1:30), stirred for 2 h to hydrolyze until clear, and a precursor solution 2 was obtained; (3) Precursor solution 2 was poured into a hydrothermal reactor so that precursor solution 2 occupied 60% of the volume of the lining, and the fiber preform (three-dimensional spacer woven fabric) was immersed in the precursor solution. Liquid 2, placed at an angle, and then placed the autoclave in an environment of 130°C to react for 15 hours; the fiber preform after the reaction was washed with deionized water until neutral, dried at 100°C for 4 hours, and then heat treated at 600°C in air for 5 hours to obtain a fiber preform with a TiO2 seed layer uniformly loaded on the fiber surface; (4) The preform with a TiO2 seed layer on the surface was immersed in precursor solution 1, reacted at 80°C, filtered and re-injected with new precursor solution 1 every 4 hours, reacted for 24 hours, taken out, washed with distilled water until neutral, dried at 100°C for 4 hours, and then heat treated at 600°C for 6 hours to obtain a modified three-dimensional spacer woven fabric.

[0069] S2. Preparation of three-dimensional spacer woven fabric / SiO2 aerogel composites: (1) Deionized water, ethanol, TEOS, and MTMS were mixed in a molar ratio of 10:4:1:2 and stirred magnetically at room temperature to make them uniformly mixed; (2) 1 ml of oxalic acid solution (0.1 mol·L) was added dropwise. -1 ) The pH value of the mixed solution was controlled at 2, and the mixed solution was sealed and placed in a 40°C water bath environment for heating and magnetic stirring for 30 min to hydrolyze the solution to obtain a sol hydrolyzate; (3) DMF (DMF to TEOS molar ratio is 0.5) was added dropwise into the sol hydrolyzate and magnetic stirring was performed for 5 min to mix evenly; 0.5 ml of ammonia solution (0.5 mol·L -1 ) to make the pH value 9, put the three-dimensional spacer woven fabric into the mold, pour in the sol hydrolyzate, stir evenly and let it stand to gel, wait until the beaker is tilted at 45℃ and the liquid surface does not flow, then add it into an aging solution with a volume ratio of TEOS to ethanol of 1:1 and age it for 72h (50℃); (4) After the aging is completed, rinse it repeatedly with n-hexane for 4 times, each time for 6h. After the rinsing is completed, place the wet gel in a mixed solution of TMCS, ethanol and n-hexane with a volume ratio of 2:1:7 for hydrophobic modification for 72h (50℃). When the wet gel is suspended in the modification solution, the modification is completed; (5) Finally, place the wet gel in a forced air drying oven, dry it at 60℃ for 6h and at 80℃ for 6h to obtain a three-dimensional spacer woven fabric / SiO2 aerogel composite material.

[0070] Comparative Example 1

[0071] A method for preparing a three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material, the preparation steps are as follows:

[0072] S1. Same as Example 1

[0073] S2. Preparation of three-dimensional spacer woven fabric / SiO2 aerogel composites: (1) Deionized water, ethanol, TEOS, and MTMS were mixed in a molar ratio of 10:4:3:1 and stirred magnetically at room temperature to make them uniformly mixed; (2) 1 ml of oxalic acid solution (0.1 mol·L) was added dropwise. -1 ) The pH value of the mixed solution was controlled at 2, and the mixed solution was sealed and placed in a 40°C water bath environment for heating and magnetic stirring for 30 min to hydrolyze the solution to obtain a sol hydrolyzate; (3) DMF (DMF to TEOS molar ratio is 0.5) was added dropwise into the sol hydrolyzate and magnetic stirring was performed for 5 min to mix evenly; 0.5 ml of ammonia solution (0.5 mol·L -1) to make the pH value 9, put the three-dimensional spacer woven fabric into the mold, pour in the sol hydrolyzate, stir evenly and let it stand to gel, wait until the beaker is tilted at 45℃ and the liquid surface does not flow, then add it into an aging solution with a volume ratio of TEOS to ethanol of 1:1 and age it for 72h (50℃); (4) After the aging is completed, rinse it repeatedly with n-hexane for 4 times, each time for 6h. After the rinsing is completed, place the wet gel in a mixed solution of TMCS, ethanol and n-hexane with a volume ratio of 2:1:7 for hydrophobic modification for 72h (50℃). When the wet gel is suspended in the modification solution, the modification is completed; (5) Finally, place the wet gel in a forced air drying oven, dry it at 60℃ for 6h and at 80℃ for 6h to obtain a three-dimensional spacer woven fabric / SiO2 aerogel composite material.

[0074] Comparative Example 2

[0075] A method for preparing a three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material, the preparation steps are as follows:

[0076] S1. Same as Example 1

[0077] S2. Preparation of three-dimensional spacer woven fabric / SiO2 aerogel composites: (1) Deionized water, ethanol, TEOS, and MTMS were mixed in a molar ratio of 10:4:1:3 and stirred magnetically at room temperature to make the mixture uniform; (2) 1 ml of oxalic acid solution (0.1 mol·L) was added dropwise. -1 ) The pH value of the mixed solution was controlled at 2, and the mixed solution was sealed and placed in a 40°C water bath environment for heating and magnetic stirring for 30 min to hydrolyze the solution to obtain a sol hydrolyzate; (3) DMF (DMF to TEOS molar ratio is 0.5) was added dropwise into the sol hydrolyzate and magnetic stirring was performed for 5 min to mix evenly; 0.5 ml of ammonia solution (0.5 mol·L -1 ) to make the pH value 9, put the three-dimensional spacer woven fabric into the mold, pour in the sol hydrolyzate, stir evenly and let it stand to gel, wait until the beaker is tilted at 45℃ and the liquid surface does not flow, then add it into an aging solution with a volume ratio of TEOS to ethanol of 1:1 and age it for 72h (50℃); (4) After the aging is completed, rinse it repeatedly with n-hexane for 4 times, each time for 6h. After the rinsing is completed, place the wet gel in a mixed solution of TMCS, ethanol and n-hexane with a volume ratio of 2:1:7 for hydrophobic modification for 72h (50℃). When the wet gel is suspended in the modification solution, the modification is completed; (5) Finally, place the wet gel in a forced air drying oven, dry it at 60℃ for 6h and at 80℃ for 6h to obtain a three-dimensional spacer woven fabric / SiO2 aerogel composite material.

[0078] Comparative Example 3

[0079] The only difference from Example 1 is that the modification process of the three-dimensional spacer woven fabric is omitted, that is, step S1 is omitted, and step S2 is directly performed with the unmodified three-dimensional spacer woven fabric.

[0080] Comparative Example 4

[0081] S1. Same as Example 1

[0082] S2. Preparation of three-dimensional spacer woven fabric / SiO2 aerogel composites: (1) Deionized water, ethanol, and TEOS were mixed in a molar ratio of 10:4:2 and stirred magnetically at room temperature to make them uniformly mixed; (2) 1 ml of oxalic acid solution (0.1 mol·L) was added dropwise. -1 ) The pH value of the mixed solution was controlled at 2, and the mixed solution was sealed and placed in a 40°C water bath environment for heating and magnetic stirring for 30 min to hydrolyze the solution to obtain a sol hydrolyzate; (3) DMF (DMF to TEOS molar ratio is 0.5) was added dropwise into the sol hydrolyzate and magnetic stirring was performed for 5 min to mix evenly; 0.5 ml of ammonia solution (0.5 mol·L -1 ) to make the pH value 9, put the three-dimensional spacer woven fabric into the mold, pour in the sol hydrolyzate, stir evenly and let it stand to gel, wait until the beaker is tilted at 45℃ and the liquid surface does not flow, then add it into an aging solution with a volume ratio of TEOS to ethanol of 1:1 and age it for 72h (50℃); (4) After the aging is completed, rinse it repeatedly with n-hexane for 4 times, each time for 6h. After the rinsing is completed, place the wet gel in a mixed solution of TMCS, ethanol and n-hexane with a volume ratio of 2:1:7 for hydrophobic modification for 72h (50℃). When the wet gel is suspended in the modification solution, the modification is completed; (5) Finally, place the wet gel in a forced air drying oven, dry it at 60℃ for 6h and at 80℃ for 6h to obtain a three-dimensional spacer woven fabric / SiO2 aerogel composite material.

[0083] Comparative Example 5

[0084] A method for preparing a three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material, the preparation steps are as follows:

[0085] S1. Surface modification of three-dimensional spacer woven fabrics as in Example 1;

[0086] S2. Preparation of three-dimensional spacer woven fabric / SiO2 aerogel composites: (1) Deionized water, ethanol, and MTMS were mixed in a molar ratio of 10:4:2 and magnetically stirred at room temperature to make them uniformly mixed; (2) 1 ml of oxalic acid solution (0.1 mol·L) was added dropwise. -1) The pH value of the mixed solution was controlled at 2, and the mixed solution was sealed and placed in a 40°C water bath environment for heating and magnetic stirring for 30 min to hydrolyze the solution to obtain a sol hydrolyzate; (3) DMF (DMF to MTMS molar ratio is 0.5) was added dropwise into the sol hydrolyzate and magnetic stirring was performed for 5 min to mix evenly; 0.5 ml of ammonia solution (0.5 mol·L -1 ) to make the pH value 9, put the three-dimensional spacer woven fabric into the mold, pour in the sol hydrolyzate, stir evenly and let it stand to gel, wait until the beaker is tilted at 45℃ and the liquid surface does not flow, then add it into an aging solution with a volume ratio of TEOS to ethanol of 1:1 and age it for 72h (50℃); (4) After the aging is completed, rinse it repeatedly with n-hexane for 4 times, each time for 6h. After the rinsing is completed, place the wet gel in a mixed solution of TMCS, ethanol and n-hexane with a volume ratio of 2:1:7 for hydrophobic modification for 72h (50℃). When the wet gel is suspended in the modification solution, the modification is completed; (5) Finally, place the wet gel in a forced air drying oven, dry it at 60℃ for 6h and at 80℃ for 6h to obtain a three-dimensional spacer woven fabric / SiO2 aerogel composite material.

[0087] Comparative Example 6

[0088] Preparation of SiO2 aerogel: (1) firstly, deionized water, ethanol, TEOS, and MTMS were mixed in a molar ratio of 10:4:1:1, and magnetically stirred at room temperature to make the mixture uniform; (2) 1 ml of oxalic acid solution (0.1 mol·L) was added dropwise. -1 ) The pH value of the mixed solution was controlled at 2, and the mixed solution was sealed and placed in a 40°C water bath environment for heating and magnetic stirring for 30 min to hydrolyze the solution to obtain a sol hydrolyzate; (3) DMF (DMF to TEOS molar ratio is 0.5) was added dropwise into the sol hydrolyzate and magnetic stirring was performed for 5 min to mix evenly; 0.5 ml of ammonia solution (0.5 mol·L -1 ) Make the pH value 9, pour in the sol hydrolyzate, stir evenly and let it stand to gel. When the beaker is tilted at 45°C and the liquid surface does not flow, add it to an aging solution with a volume ratio of TEOS to ethanol of 1:1 and age it for 72 hours (50°C); (4) After aging, rinse it repeatedly with n-hexane for 4 times, each time for 6 hours. After rinsing, place the wet gel in a mixed solution of TMCS, ethanol and n-hexane with a volume ratio of 2:1:7 for hydrophobic modification for 72 hours (50°C). When the wet gel is suspended in the modification solution, the modification is completed; (5) Finally, place the wet gel in a forced air drying oven and dry it at 60°C for 6 hours and at 80°C for 6 hours to obtain pure SiO2 aerogel. See the actual picture Figure 2 .

[0089] The performance of the aerogel composite materials prepared in Examples 1-3 and Comparative Examples 1-6 was tested, and the test results are shown in Table 1.

[0090] Table 1

[0091]

[0092] Note: The compressive strength test method refers to the standard GB / T 1041-2008; the thermal conductivity test method refers to the standard ISO22007-2.

[0093] It can be seen from Table 1 that, compared with pure SiO2 aerogel (Comparative Example 6), the aerogel composite materials prepared in Examples 1-3 have significantly improved compressive strength and tensile strength while retaining a larger specific surface area and a smaller thermal conductivity; Comparative Examples 1-2 and 4-5 changed the composition of the composite silicon source, and the gel network changed, so the specific surface area was slightly reduced, and at the same time, the tensile strength and compressive strength were also reduced; and in Comparative Example 3, the three-dimensional spacer woven fabric was not modified, which affected the bonding strength between the reinforcing material and the matrix, thereby resulting in the overall mechanical properties of the material.

[0094] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material, characterized in that: Firstly, the surface of the three-dimensional spacer woven fabric is modified by a seed-induced solvothermal method so that a TiO2 nanoarray grows on the surface of the three-dimensional spacer woven fabric to obtain a modified three-dimensional spacer woven fabric; then, methyltrimethoxysilane and tetraethoxysilane are used as a composite silicon source and the modified three-dimensional spacer woven fabric is used as a reinforcing material to obtain the three-dimensional spacer woven fabric-reinforced SiO2 aerogel composite material by a sol-gel method.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the methyltrimethoxysilane to the tetraethoxysilane is 1:(0.5-2).

3. The preparation method according to claim 1, characterized in that: The preparation steps of the modified three-dimensional spacer woven fabric include: (1) adding melamine and nitric acid to a H2O2 solution, stirring until it becomes clear, adding a titanium sheet and stirring until a reddish brown precursor solution 1 is obtained; (2) adding tetrabutyl titanate dropwise into a hydrochloric acid aqueous solution, stirring and hydrolyzing until clear, to obtain a precursor solution 2; (3) immersing the three-dimensional spacer woven fabric in the precursor solution 2, placing it at an angle, performing a hydrothermal reaction, washing, drying, and performing a first heat treatment in an oxygen-containing atmosphere to obtain a three-dimensional spacer woven fabric with a TiO2 seed crystal layer uniformly loaded on the fiber surface; (4) Immersing the three-dimensional spacer woven fabric with a TiO2 seed crystal layer on its surface in the precursor solution 1, heating for reaction, repeatedly filtering and injecting new precursor solution 1, drying after the reaction is complete, and performing a second heat treatment to obtain the modified three-dimensional spacer woven fabric.

4. The preparation method according to claim 3, characterized in that: The temperature of the first heat treatment is 400-550° C., and the time is 5-6 hours; and / or, the oxygen-containing atmosphere is an air atmosphere.

5. The preparation method according to claim 3, characterized in that: The concentration of the hydrochloric acid in step (2) is 26.7 Vol%; the volume ratio of the tetrabutyl titanate to the hydrochloric acid aqueous solution is 1:30; and / or, The hydrolysis time is 2h.

6. The preparation method according to claim 3, characterized in that: The conditions of the hydrothermal reaction are: reacting at 120-140° C. for 14-16 hours; and / or, the temperature of the second heat treatment is 450-600° C. for 6-7 hours.

7. The preparation method according to claim 1, characterized in that: The steps for preparing the three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material by the sol-gel method include: (1) adding acid to the composite silicon source solution to adjust the pH value to 2-3, heating and hydrolyzing to obtain a hydrolyzate; (2) dripping DMF dropwise into the hydrolyzate under stirring conditions, and then adding alkali to adjust the pH value of the hydrolyzate to 8-9; (3) placing the modified three-dimensional spacer woven fabric into a mold, pouring in the hydrolyzate, stirring evenly and letting it stand to gel, and then aging; (4) washing the aged gel and hydrophobically modifying it; and (5) drying to obtain the three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material.

8. The preparation method according to claim 7, characterized in that: The hydrolysis temperature is 40-45°C and the time is 30-35 minutes; and / or, The aging conditions are: adding the gel to an aging solution having a volume ratio of TEOS to ethanol of 1:1 at 50° C. and aging for 72 hours; and / or, The hydrophobically modified modification liquid is a mixed solution of TMCS, ethanol and n-hexane in a volume ratio of 2:1:7, and the modification time is 72 hours; and / or, The drying conditions of step (5) are as follows: placing the wet gel in a forced air drying oven and drying it at 60° C. for 6 h or at 80° C. for 6 h.

9. A three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material, characterized in that: The preparation method is described in any one of claims 1 to 8.

10. Use of the three-dimensional spacer woven fabric reinforced SiO2 aerogel composite material as claimed in claim 9 as a thermal insulation material.